(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
This article presents the formulation of some mixed problems for an equation of the third-order composite type. Under certain conditions, the correctness of these problems in S. L. Sobolev spaces is proved for the coefficients and the right-hand side of the equation. Keywords: mixed boundary value problems, equations of composite type, theorem, cylindrical domain, regular problems, differential equation, S.L. Sobolev spaces, Green’s formula